Synthesis and biological evaluation of a 99mTc-labelled cyclic RGD peptide for imaging the αvβ3 expression - Haubner, R.; Bruchertseifer, F.; Bock, M.; Kessler, H.; Schwaiger, M.; Wester, H.-J. (Nuklearmedizin - NuclearMedicine, 2004)
Aim: The αvβ3 integrin is involved in tumour induced angiogenesis and tumour metastasis. We describe the synthesis and evaluation of a 99mTc-labelled RGD analogue for the visualisation of αvβ3 integrin expression. Methods: The linear peptides were assembled on a solid support. Cyclisation was performed under high dilution conditions. For conjugation with the chelator peptide, a water soluble carbodiimide was used. Radiolabelling was carried out due to standard procedures with high radiochemical yield and radiochemical purity. For in vivo evaluation, nude mice bearing αvβ3-positive human melanoma M21 and αv-negative human melanoma M21-L or Balb/c mice bearing αv-positive murine osteosarcoma were used. Results: Activity accumulation of 99mTc-DKCK-RGD 240 min p. i. was 1.1% ID/g in the αvβ3-positive melanoma and 0.3% ID/g in the negative control tumour. In the osteosarcoma model 2.2% ID/g was found 240 min p. i. Planar gamma camera images allowed contrasting visualisation of αvβ3-positive tumours 240 min p. i. Blocking of the tumour using the αvβ3-selective pentapeptide cyclo(-ArgGly-Asp-D-Phe-Val-) reduces activity accumulation in the tumour to background level. However, 240 min p. i. highest activity concentration was found in kidneys resulting in low tumour/kidney ratios. Metabolite analysis 240 min p. i. showed approximately 60% intact tracer in kidneys and 80% in the tumour. Only 24% intact tracer was found in blood 30 min p. i. Conclusion: 99mTc-DKCK-RGD allows imaging of αvβ3-positive tumours in mice. However, pharmacokinetics as well as metabolic stability of the tracer have to be improved for potential clinical application.
Keywords: RGD-peptides; alpha(v)beta3; integrin; stability; angiogenesis; tumor targeting